The scale of seasonal migrations in the urban part of the Great Tit population in the southeast of the West Siberian plain - I. G. Frolov (Юг России: экология, развитие, 2022)
Aim. This research aims to study the Great Tit breeding density, depending on the distance from preferred wintering sites with all other things being equal.Material and Methods. 36 route counts were carried out in 22 locations ranging up to 95 km away from the preferred wintering sites. The data was collected in the same weather and climatic zone. The route counts were carried out in the wintering season (January) and in the breeding season (16 April – 15 May) in 2014‐2018. To consider the influence of small settlements, where a smaller number of tits spends winter in comparison with a large city, sample sites were characterized by the population of people living within a radius of 25 km around the sample site.Results. Most Great Tits prefer to minimise the distance from their wintering sites to their nesting sites. The most preferred distance of seasonal movement is 10‐20 km from a large city, the main wintering place for this species.Conclusions. The density of the Great Tit population during the nesting period increases exponentially with the proximity of wintering sites. When more than 20 km from wintering sites, the density of the species during the nesting period does not change reliably. The maximum immanent density during the nesting period is achieved in places of favourable wintering of the species, that is, in a metropolis with agglomeration.